THE IMPLEMENTATION OF QUIZZIZ AS AN ENGLISH LANGUAGE LEARNING ASSESSMENT TOOL - Hanani, Muhammad Dzakir Aslam; Sari, Raras Hafidha; Ambarwati, Suci (Teaching English as Foreign Language, Literature and Linguistics, 2024)
This study explores the implementation of Quizizz as an assessment tool for English language learning. The study highlights Quizizz's potential to enhance student engagement and motivation through its interactive, game-based format. Employing a mixed-method approach, this research involved planning and execution stages to observe the impact of Quizizz on students' understanding of "Obligation and Necessity." Findings indicate that Quizizz not only increases student participation but also provides immediate feedback, aiding both students and teachers in assessing comprehension and areas for improvement. Challenges, such as limited digital access and technical literacy, were addressed through supportive interventions. This research supports Quizizz as an effective, engaging assessment medium, offering recommendations for future improvements in digital learning assessments. Keywords: digital learning; English assessment; interactive quiz; Quizizz; student engagement.